Launching Public Private Partnerships for Highways in Transition Economies - Queiroz, Cesar (World Bank, Washington, DC, 2014)
In many countries the private sector has been involved in financing infrastructure through concessions under a public-private partnership (PPP) program. PPP schemes, however, are somewhat underutilized in transition economies, where the potential financing gaps are significant and growing, and there seems to be an enormous potential for more private sector involvement in the financing and operation of highway assets in these countries. Institutions such as the World Bank can contribute to enhance private financing of road infrastructure through greater use of their guarantee power, in addition to supporting, when required, the public sector contribution to the construction cost of a PPP project through loans. Partial risk guarantees are particularly relevant in the context of seeking more private involvement in the financing of road infrastructure. This paper reviews potential applications of partial risk guarantees, the required legal framework (for example, concession law) for attracting private capital for PPP schemes, possible steps for a country to launch a program of private participation in highways, the concept of greenfield and road maintenance concession programs, and the treatment of unsolicited proposals. It also summarizes potential applications of the World Bank Toolkit for PPP in Highways as an instrument to help decision-makers and practitioners to define the best PPP approach for a specific country.